The Criminalization of Marital Rape as a Criminal Offense of Sexual Violence: A Comparative Analysis of Criminal Law in Indonesia, Malaysia, and Brunei Darussalam - Siti Maymanatun Nisa; Siti Umi Zuhliah Muhraeni R; Aryo Salasa (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
Marital rape constitutes a form of sexual violence within marriage that continues to remain concealed behind patriarchal cultural norms, which position sexual obligations as the absolute right of the husband. Although globally recognized as a violation of human rights, the legal recognition of sexual coercion committed by a husband varies significantly across jurisdictions. This research is grounded in the increasing incidence of gender-based violence in Indonesia, Malaysia, and Brunei Darussalam, as well as the absence of an in-depth comparative study concerning the legal framework governing marital rape in these three countries, which share closely related historical, cultural, and family law traditions. This study employs a normative-juridical approach combined with comparative legal analysis. It integrates Feminist Legal Theory as an analytical framework to examine unequal power relations within marriage and Comparative Law Theory to assess differences in legal regulations and the effectiveness of legal protection mechanisms. The data were obtained from statutory regulations, court decisions, academic literature, and official national and international reports. The findings of this study demonstrate, among others, that: (1) the urgency of regulating marital rape lies not merely in recognizing it as a criminal offense, but also in the necessity for the law to rectify unequal power relations within marriage. In the absence of clear legal regulation, sexual coercion within the household will continue to remain hidden, underreported, and inadequately prosecuted. (2) Indonesia has adopted the most progressive approach by recognizing sexual coercion within marriage as a criminal offense through the Law on Sexual Violence Crimes and the 2023 Criminal Code. Malaysia continues to maintain the marital rape exemption, thereby allowing criminal liability only in cases involving physical violence. Brunei Darussalam remains the most restricted.